Communicative action and practical discourse to empower patients in healthcare-related decision making - Napiwodzka, Karolina (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2021)
The aim of the paper is to reconsider Habermas’ discourse approach in terms of its usefulness in the realm of public healthcare where, on a microscale, intersubjective communicative situations arise between defined participants, i.e., patients and healthcare providers, patients’ family members, and further eligible contributors to patient-related decision making. A need for more “communicative interaction,” and explicative and practical discourse, is illustrated by two empirical examples of medical decision making which reveal both communicative and discursive deficits (Section I). To empower and enable the patient as a rational and autonomous speaker and discourse participant, a Habermasian emancipatory argument and ‘the power of the better argument’ is recalled (Section III). The possibility of equal communicative and discursive rights in the light of real inequalities is discussed in the context of a ‘competence gap’ between participants (Section IV). Further sections focus on the importance of informed consent on the side of the patient and the communicative competences as an important factor of healthcare system.